Promosi Kesehatan Pemberian ASI Eksklusif terhadap Pengetahuan dan Sikap Ibu Hamil - Rotua Sumihar Sitorus (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Stunting is a disruption of physical development that has passed with decreasing in the growth rate of children. Puskesmas Pancur Batu conducts stunting prevention through health promotion to increase knowledge and attitudes of pregnant women about exclusive breastfeeding. The number of mothers giving exclusive breastfeeding only reached 44.9% (target 80%). The purpose of the study was to analyze the effect of health promotion with leaflet media about exclusive breastfeeding on the knowledge and attitudes of pregnant women in stunting prevention. The study design was quasi-experimental with a sample of 40 pregnant women. The study was conducted in October 2019 in Puskesmas Pancur Batu. The sampling technique is done purposively. Data were analyzed using independent t test. The results showed that before the pre-test, the average score of knowledge variables from the intervention group 6.60 and the comparison group 6.22, after the post-tes increased to 10.30 and 8.34. The average score of attitude variables from the intervention group was 4.04 and the comparison group was 4.44, after the post-test increased to 5.80 and 4.84. The results of the statistic test showed that health promotion influences the knowledge and attitude of pregnant women in preventing stunting before and after the intervention with p = 0.005 and p 0.028 <0.05. It is recommended that Puskesmas staff conduct health promotion through the distribution of leaflets to facilitate pregnant women in understanding the benefits of exclusive breastfeeding in an effort to prevent stunting.